A Mini Review of Antibacterial Properties of Al2O3 Nanoparticles - Sergey V. Gudkov; Dmitriy E. Burmistrov; Veronika V. Smirnova; Anastasia A. Semenova; Andrey B. Lisitsyn (Nanomaterials, 2022)
Bacterial antibiotic resistance is one of the most serious modern biomedical problems that prioritizes the search for new agents to combat bacterial pathogens. It is known that nanoparticles of many metals and metal oxides can have an antibacterial effect. However, the antibacterial efficacy of aluminum oxide nanoparticles has been studied little compared to the well-known antimicrobial properties of nanoparticles of oxides of metals such as zinc, silver, iron, and copper. In this review, we have focused on the experimental studies accumulated to date demonstrating the antibacterial effect of aluminum oxide nanoparticles. The review discusses the main ways of synthesis and modification of these nanoparticles, provides the proposed mechanisms of their antibacterial action against gram-positive and gram-negative bacteria, and also compares the antibacterial efficacy depending on morphological characteristics. We have also partially considered the activity of aluminum oxide nanoparticles against water microalgae and fungi. In general, a more detailed study of the antibacterial properties of aluminum oxide nanoparticles is of great interest due to their low toxicity to eukaryotic cells.